ESTETIKA TARIAN SARA DOUDA DALAM MASYARAKAT ADAT LOLI (SEBUAH PENDEKATAN LINGUISTIK KEBUDAYAAN) - Sulistyastuti Sutomo (PAROLE: Journal of Linguistics and Education, 2014)
Not only does art   have   self-fullfillment, but  it also has axiological  benefits both socially, culturally, religiously, and economiclally.  So does Sara Douda dance.  Sara Douda aesthetics  is first contained  in its whole dance movements. In addition, it  can also be found in the whole dance equipments.  Moreover,  this dance aesthetics  may  also be contained in the verbal symbols in the speech forms  prior to the dance performance. However,  both verbal and non-verbal aesthetical forms are incorporated by the pieces of socio-cultural and  religious values in the Loli community about  their honoring their ancestors,  having social harmony, and  highly respecting each other among the community members. This study uses a cultural linguistic approach to find out and to review the aesthetics of Sara Douda dance.   Seni memang memiliki kepenuhan dalam dirinya sendiri. Tetapi ia juga sekaligus punya faedah aksiologis, baik secara sosial, kultural, religius maupun secara ekonomis. Tarian Sara Douda pun demikian. Estetika Sara Douda pertama-tama ada dalam semua gerak tariannya. Juga dalam seluruh perlengkapan tarian tersebut. Bukan itu saja, estetika tarian ini juga ada dalam simbol-simbol verbal berupa tuturan menjelang tarian. Tetapi baik bentuk-bentuk estetisasi nonverbal maupun verbal, sama-sama disatukan oleh kepingan-kepingan nilai-nilai sosio-kultural dan religius masyarakat Loli tentang penghormatan kepada leluhur, tentang harmoni sosial, dan tentang penghargaan yang tinggi terhadap satu sama lain. Penelitian ini menggunakan pendekatan linguistik kebudayaan demi menemukan dan menelaah estetika dalam tarian Sara Douda